Pursuing Respect in the Cannibal Isles : Americans in Nineteenth-Century Fiji - Shoemaker, Nancy, 1958- (Book collections on Project MUSE., 2019)
"The aspirations of individual Americans to be recognized as people worthy of respect was a driving force in the vast global expansion launched by the United States shortly after the nation's founding. This book explore the perspectives of three Americans in Fiji"--